Manajemen Cuci Tangan Efektif Untuk Mencegah Penyakit Menular Pada Anak Usia Sekolah - Atikah, Nurul; Abqariah; Miniharianti (Yayasan Sagita Akademia Maju, 2024)
Washing hands is one effort to break the chain of disease transmission to school-age children. So that school children can manage hand washing effectively. This will make it a routine habit taught as early as possible. There are many methods and ways of teaching by playing and exploring the environment around the school. Based on observations made, school children rarely wash their hands before eating food bought in the school canteen. This case study aims to implement effective hand-washing management to prevent infectious diseases in school-aged children. The service was carried out for school-age children at SD N 1 Layan, Tangse District, Pidie Regency with 72 students using a workshop method that included 6 effective hand-washing management steps. It is hoped that there will be an increase in the awareness of school children to be able to wash their hands to prevent infectious diseases and to improve the health status of Indonesian children